Obtaining an Empirical Earthquakes Duration Magnitude Formula from the Data of the Iraqi Meteorological Organization and seismology (IMOS) - Mahmmoud, Zainab Hussain; Al-Rahim, Ali M. (Iraqi Journal of Science, 2023)
This paper calculated the Duration Magnitude (MD) equation using data from the Iraqi Meteorological Organization and seismology (IMOS). It is an empirically determined equation and expressed as: The epicentral distance and local geological conditions affect the duration of the coda. The data is obtained from 7 seismic stations in the network. The new proposed duration magnitude equation results from applying linear regression analysis to the data of a seismic signal duration with correlation coefficient R2=0.76; and a standard deviation value of 0.049. Station corrections indicated by Sc are also specified for the seismic stations that range from -0.024 to + 0.02.